Girls on the brink : helping our daughters thrive in an era of increased anxiety, depression, and social media - Nakazawa, Donna Jackson (Harmony Books, 2022)
"Anyone on the front lines of caring for girls today--parents, school nurses, guidance counselors--knows that girls are more anxious and more prone to depression and self-harming than ever before. New science confirms this a biologically-rooted phenomenon, set in motion by the earlier onset of puberty, the evolutionary predisposition of the female brain to react to perceived threats, and the many new social pressures (like social media and entrenched societal sexism) girls are subjected to. Indeed, as award-winning writer Donna Jackson Nakazawa deftly explains in Girls on the Edge, during the critical neurodevelopmental window of adolescence, these factors may be altering the female stress-immune response in ways that derail thriving. But our new understanding of modern girlhood yields very good news, too. We know now that a girl's innate sensitivity to her environment can, with the right conditions, become her superpower. And from recent studies and trial interventions, we now know the key components of preventing mental health concerns in girls as well as helping those who are already struggling. Drawing on insights from both the latest science and girls themselves, Jackson Nakazawa guides parents through fifteen "antidote" strategies to help her thrive in the face of stress, including ways parents can create a safe harbor at home, how they can engage the power of a mentor to help their daughter feel she matters, and how to help her find a sense of "something bigger" to focus her attention in positive ways. Neuroprotective and healing, the strategies in Girls on the Edge amount to a new playbook for how we--parents, families, and the human tribe--can secure a healthy emotional inner life for all of our girls"--